Payment system and bank performance: Evidence from Vietnam - TRAN, MANH HA (The journal of contemporary issues in business and government, 2021)
This paper investigates the relationship between the business of payment system and the performance of banking industry in Vietnam. Using data of 20 listed banks from 2009 to 2019, we find that the innovations in mobile payment have significant impact on bank performance, while the traditional types of payment show little evidence. We also argue that payment system in Vietnam does not contribute much to the stability of banks’ performance.